¬PENGARUH SOCIAL MEDIA INFLUENCER TERHADAP PURCHASE INTENTION YANG DIMEDIASI OLEH TRUSTWORTHINESS (STUDI PADA AKUN INSTAGRAM @KULINERSBY) - Purwanto, Albin Sayyid Agnar Caesar; Purwanto, Teguh (Fakultas Ekonomi Universitas PGRI Adi Buana, 2019)
Indonesia is the country with the most monthly active users in Asia Pacific region. This can be an opportunity for businesses to market, promote, or advertise their products through Instagram. Marketers must be smart to find the best way to influence consumers by disguising the advertisements they want to convey so that consumers don’t consider it as noise or interference. This is where the role of influencers is useful, to disguising advertisements. Influencers are